PERANCANGAN SISTEM INFORMASI PENDAFTARAN PADA TK ISLAM BUDAYA I BERBASIS WEB - Lovya Neysa Jayati (2021)
Every year, the school always accepts new students to select prospective students who will register. TK Islam Budaya I is one of the schools in Jakarta that accepts new students. The registration process carried out by the Islamic Cultural Kindergarten 1 still uses the manual method, which is still using brochures and paper forms. This can cause several obstacles, namely loss of data and take a long time to input the data contained in the form. From these problems, a registration information system is needed that can reduce the obstacles that might occur in the previous system. The registration information system contains the registration process starting from providing registration information, filling out forms, checking data, and reporting on the results of the selection in the form of a website application. HTML and PHP will be used in making the website. The results of the research on the registration information system at the Islamic Cultural I Kindergarten I based on this website can simplify and assist in the registration process.